Análise do campo de conhecimento relativo a usuários de biblioteca - Odilia Clark Peres Rabello (1981)
The field of knowledge related to library users, part of discipline Librarianship, was studied as a first approach to the study of teaching programs of the area. As an introduction, the philosophy of education for librarianship, with enfasis in user studies, was discussed. The study of analysis of the field contents presented two discrete aspects: proposal of analysis of the field and its basic contents based on a theoretic reference and on the exmination of the intellectual production of the area, aiming at the establishment of a point of liaison between them. It was concluded that the object of study is the interaction user/library and that its basic contents, around which the field is structured, refer to individuals and groups, social and cultural environement, needs and motivation, interation/behavior, comunication and library. Suggestions for a posterior development of programs on the area were made.